Is the sponge a bob? a study on children's perception of gender as presented in the cartoon series Spongebob Squarepants - Migriño, Erika Paola Maputi 1989-; Canlas, Daphne-Tatiana T. (Quezon City College of Mass Communication, University of the Philippines Diliman, 2011)
"This study addressed how seven-year-old children perceived gender based on physical and behavioral indicators shown in the episode Rock-a-Bye Bivalve of the series Spongebon Squarepants. The research aimed to determine children's reactions to gender indicators shown in the episode and to relate these reactions with the children's notions of gender roles and their perception of gender. The researcher pursued the study in order to determine if the message of breaking the gender roles was getting through to the program's target audience. With Symbolic Interactionism and Queer Theories providing the theoretical basis for the study, the researcher conducted textual analysis to determine the particular indicators, participant observation to note the children's reactions, and focus interviews to substantiate the reactions and determine how they perceived SpongeBob Squarepants' gender. The researcher found that Spongebob Squarepants is a form of media that tries to slowly chip at the existing gender norms by presenting gender-bending images. Meanwhile, children's perceptions of Spongebob's gender vary on the basis of which indicator they take notice of and how they understand gender norms based on their interactions with their immedaite society. However, these findings cannot be applied to the general population, given the qualitative design of this research."
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman